Bahan Ajar Alat Ukur dan Pengukuran Fisika Berbasis Inkuiri Terbimbing - Ino Angga Putra; Eko Sujarwanto (Pascasarjana Universitas Negeri Malang (UM), 2016)
Abstract: This research to determine the feasibility, effectiveness of teaching materials measuring instrument and measurement physics in increasing science process skills and mastery of concepts students. The research design using the design development of Borg & Gall. The effectiveness of teaching materials tested under 2 steps, before the mid-term exam and final exam of the semester. The research showed that the teaching materials of measurement and instrument measurement of physics-based guided inquiry developed,: 1) is under fairly feasible category to be implemented, 2) adequates to improve the process science skills of students, 3) improves mastery of concepts. Step one indicates the presence of correlation between science process skills and mastery concept of the students. The next step shows no correlation between them.Key Words: teaching materials based on guided inquiry, physics measurement and measurement instrument Abstrak: Penelitian ini bertujuan untuk mengetahui kelayakan, keefektifan bahan ajar alat ukur dan pengukuran fisika dalam meningkatkan keterampilan proses sains dan penguasaan konsep mahasiswa. Desain penelitian menggunakan desain pengembangan Borg & Gall. Keefektifan bahan ajar diuji dalam 2 tahap, yakni menjelang ujian tengan semester dan sebelum ujian akhir semester. Hasil penelitian menunjukkan bahwa bahan ajar alat ukur dan pengukuran fisika berbasis inkuiri terbimbing yang telah dikembangkan memiliki karakteristik: 1) dalam kategori cukup layak untuk diimplementasikan, 2) meningkatkan keterampilan proses sains mahasiswa, 3) meningkatkan penguasaan konsep. Tahap satu menunjukkan terdapatnya korelasi antara keterampilan proses sains dan penguasaan konsep mahasiswa. Tahap dua menunjukkan tidak terdapat korelasi antara keterampilan proses sains dengan penguasaan konsep.Kata kunci: bahan ajar berbasis inkuiri terbimbing, alat ukur dan pengukuran fisika